Description of a new species of the cardinalfish genus Pseudamiops (Perciformes, Apogonidae) from the Red Sea - Gon, Ofer; Bogorodsky, Sergey V.; Mal, Ahmad O. (Zootaxa, 2013)
A new species of pseudamine cardinalfish, Pseudamiops springeri, is described from five specimens collected in the Red Sea. It may be distinguished from the four known species of Pseudamiops in having 13 pectoral-fin rays, pseudobranch with 2–4 filaments, no canine teeth on the vomer, anterior nostril with a conspicuous skin flap and genital opening flanked by two slender papillae. Pseudamiops springeri is closest to its Western Indian Ocean congener P. pellucidus Smith.